A case-control study of human papillomavirus and cervical squamous intraepithelial lesions (SIL) in Harris County, Texas: differences among racial/ethnic groups - Tortolero-Luna Guillermo; Mitchell Michele Follen; Swan David C.; Tucker Ruth Ann; Wideroff Louise; Icenogle Joseph P. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
We conducted a case-control study of the association between SIL and HPV among whites (W), African Americans (AA), and Hispanics (H) in Harris County, Texas. Cases were identified at M.D. Anderson Cancer Center Colposcopy Clinic. Controls were identified among women obtaining routine Pap screening at two Harris County Health Department Clinics. HPV was detected by a PCR-based fluorescent assay. Dichotomous and polytomous logistic regression models were used to estimate adjusted odd ratios (AOR) and 95% confidence intervals (CI) for SIL among racial/ethnic groups and grade of disease. Prevalence of HPV infection was 64% in low grade SIL (LSIL), 84% in high grade SIL (HSIL), and 19% in controls. Risk of SIL was higher in H than in W and AA, AOR 29.5 (12.4-70.5), 15.3 (6.0-33.8), and 5.8 (2.6-12.6), respectively. Similarly, racial/ethnic differences were observed for both LSIL (AOR = 16.6, 7.7, and 4.3, respectively) and HSIL (AOR = 78.6, 34.6, and 14.2, respectively). Findings support the association between SIL and HPV and differences in the strength of the association with LSILs and HSILs. Data also suggest a higher risk for H and a lower risk for AA.